FUNGSI SUPERVISI PENDIDIKAN PADA SEKOLAH UMUM DAN MADRASAH - Muhammad Bahrudin (JIP: Jurnal Ilmu Pendidikan, 2024)
Educational supervision plays an important role in ensuring the quality of the teaching and learning process in public schools and madrasahs. The function of supervision focuses on improving the competence of educators, overseeing the implementation of the curriculum, and professional development. In addition, supervision serves to monitor, evaluate and provide constructive feedback to ensure that educational goals are achieved effectively and efficiently. In public schools, educational supervision tends to focus on the implementation of the national curriculum, the development of teaching methods, and the monitoring of student learning outcomes. Meanwhile, in madrasah, supervision places more emphasis on the integration of academic education and religious values. Despite differences in approach, the two institutions share the same goal of improving the quality of education provided to students.